Design of double stator arc type permanent magnet generator for oil palm mechanical cutter application - Che Ahmad, Suhairi Rizuan (2012)
Over the past few years, the usage and demand of portable generators are very high. In accordance with its lightweight, small size, easy to carry anywhere and can provide high power; it becomes necessary for everyone to have it. There are various types of portable generators in the market, but mostly for use in homes, commercial and industrial. Only a few of them are design for agriculture application. Therefore, a portable power supply with a small size and lightweight of Permanent Magnet Generator (PMG) for the agricultural sector is proposed. In this research, the Permanent Magnet Generator (PMG) will be applied as a part of new palm oil mechanical cutter system. A lot of research regarding previous work that has been done by others and the characteristic and performance of the PMG is described in literature. However, none of them focus on PMGs intended to be used for agricultural application whereas the typical requirement is of high-power capability, small and ease of use. Recently, there were some existing products developed for palm oil mechanical cutter. Due to the drawbacks of the existing mechanical cutter are extra weight and limited height. The improvement of this mechanical cutter by using PMG to supply the mechanical motor that will convert rotational to linear motion for harvesting works. The new system of palm oil mechanical cutter employs the Permanent Magnet Generator (PMG) which is can operates in a single-phase, slot type with a double stator, and with arc type permanent magnet that embedded in the rotor. This PMG aimed to produce 500W at a speed 3000 revolution per minute (rpm). This PMG will attach with a single cylinder two stroke engine (Stihl KM 85) with 0.95kW capacity. The engine will act as a prime mover to this PMG. At the same time, in order to evaluate on the best possible PMG that can be used for this application, new design and analysis on the developed PMG is required. This thesis addresses the above issue and discusses the choice of PMG for used in palm oil mechanical cutter application. A Permanent Magnet Generator is designed with a double stator, and the rotor consists of arc type permanent magnet in order to maximize its usage of flux. This new design of generators are fabricated and tested experimentally to see their output power capability. The design optimization is done by varying the size of permanent magnet, it is to ensure the magnetic flux density is considered to determine the amount of hysteresis and eddy current losses and thus the effects of the total output power that can be generated by the PMG. As a conclusion, the proposed design produced the highest output power and efficiency that can be used for palm oil mechanical cutter system.